2012
DOI: 10.1063/1.4752417
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a strong laser field on Coulomb explosion and stopping power of energetic H3+ clusters in plasmas

Abstract: The influence of a high-intensity laser field on the Coulomb explosion and stopping power for a swift H þ 3 cluster ion in a plasma target is studied by means of the molecular dynamic (MD) method based on the linearized Vlasov-Poisson theory. Excitations of the plasma are described by the classical plasma dielectric function. In the presence of the laser field, the general expressions for the induced potential in the target and the interaction force among the ions within the cluster are derived. Based on the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…It has been shown that the projectile particles can be even accelerated in a plasma due to the parametric effects excited by an intense laser field. Furthermore, Wang et al (2002Wang et al ( , 2012 have studied the influence of a high-intensity laser field on the Coulomb explosion and stopping power for a swift H + 3 cluster ion in a plasma target. They have demonstrated that the laser field affects the correlation between the ions and contributes to weaken the wake effect as compared to the laser-free case.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the projectile particles can be even accelerated in a plasma due to the parametric effects excited by an intense laser field. Furthermore, Wang et al (2002Wang et al ( , 2012 have studied the influence of a high-intensity laser field on the Coulomb explosion and stopping power for a swift H + 3 cluster ion in a plasma target. They have demonstrated that the laser field affects the correlation between the ions and contributes to weaken the wake effect as compared to the laser-free case.…”
Section: Introductionmentioning
confidence: 99%